2021
DOI: 10.1177/09603271211041667
|View full text |Cite
|
Sign up to set email alerts
|

DAPK1 may be a potential biomarker for arterial aneurysm in clinical treatment and activated inflammation levels in arterial aneurysm through NLRP3 inflammasome by Beclin1

Abstract: Background Death-associated protein kinase (DAPK1) is one of the positive regulators of apoptosis, and it is widely involved in apoptosis induced by multiple pathways. We examined that the function of DAPK1 in Clinical treatment of arterial aneurysm and its underlying mechanisms. Arterial aneurysm is a common cerebrovascular disease with high disability and fatality rate. Objectives Male C57BL/6 mice or DAPK1−/− mice were injected with 50 mg/kg pentobarbital sodium and then were injected with angiotensin II (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Average daily caloric of liquid intake per mouse was monitored and calculated in Figure S1. After 12 h of fasting, mice were anesthetized with pentobarbital solution (50 mg/kg body weight) ( 16 ). Livers and adiposes were dissected quickly, washed twice with saline, blotted dry on a filter paper, and their weights were measured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Average daily caloric of liquid intake per mouse was monitored and calculated in Figure S1. After 12 h of fasting, mice were anesthetized with pentobarbital solution (50 mg/kg body weight) ( 16 ). Livers and adiposes were dissected quickly, washed twice with saline, blotted dry on a filter paper, and their weights were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were kept in an environment of 55 ± 5% relative humidity, 23 ± 2 • C, and 12 h light and dark cycles. After 1-week acclimatization, mice were divided into (16). Livers and adiposes were dissected quickly, washed twice with saline, blotted dry on a filter paper, and their weights were measured.…”
Section: Animals Experimental Design and Sample Preparationmentioning
confidence: 99%
“…DAPK1 is methylated at CpG islands in several tumors, and based on this view it can be used as a biomarker for cancer detection and treatment . In addition, promoter hypermethylation leads to the silencing or loss of expression of DAPK1, which has been detected in several tumor cells. , What’s more, poor clinical prognosis and advanced disease in nonsmall cell lung cancer (NSCLC) patients are closely related to DAPK1 promoter hypermethylation. Furthermore, studies have shown that lymph node involvement and DAPK1 promoter hypermethylation are involved in the development of gastric cancer (GC) and head and neck squamous cell carcinoma (HNSCC) , (Table ).…”
Section: The Dapk Family In Diseasesmentioning
confidence: 99%
“…Although the impact of the mitochondrial disorder on the induction and maintenance of spinal oxidative stress and inflammatory cytokine accumulation has previously been reported, the underlying mechanism remains unclear [ 1 , 2 ]. AMP-activated protein kinase (AMPK), a strongly conserved and highly expressed eukaryotic protein serine/threonine kinase, is capable of sensing changes in body energy and has a crucial role in modulating mitochondrial function [ 3 ], combating oxidative stress and inflammation [ 4 ]. DEX, an α 2-adrenoceptor agonist, has calming, anxiolytic, and antalgic properties with minimal respiratory inhibition [ 5 ].…”
Section: Introductionmentioning
confidence: 99%